Caring touch as a bodily anchor for patients after sustaining a motor vehicle accident with minor or no physical injuries - a mixed methods study. Issue 1 (December 2016) - Airosa, Fanny; Arman, Maria; Sundberg, Tobias; Öhlén, Gunnar; Falkenberg, Torkel
Abstract Background Patients who sustain a motor vehicle accident may experience long-term distress, even if they are uninjured or only slightly injured. There is a risk of neglecting patients with minor or no physical injuries, which might impact future health problems. The aim of this study was to explore patients' subjective experiences and perspectives on pain and other factors of importance after an early nursing intervention consisting of "caring touch" (tactile massage and healing touch) for patients subjected to a motor vehicle accident with minor or no physical injuries. Methods A mixed method approach was used. The qualitative outcomes were themes derived from individual interviews. The quantitative outcomes were measured by visual analogue scale for pain (VAS, 0-100), sense of coherence (SOC), post-traumatic stress (IES-R) and health status (EQ-5D index and EQ-5D self-rated health). Forty-one patients of in total 124 eligible patients accepted the invitation to participate in the study. Twenty-seven patients completed follow-up after 6 months whereby they had received up to eight treatments with either tactile massage or healing touch. Results Patients reported that caring touch may assist in trauma recovery by functioning as a physical "anchor" on the patient's way of suffering, facilitating the transition of patients from feeling as though their body is "turned off" to becoming "awake". By caring touch the patients enjoyed a compassionate care and experience moments of pain alleviation. The VAS pain ratings significantly decreased both immediately after the caring touch treatment sessions and over the follow-up period. The median scores for VAS (p < 0.001) and IES-R (p 0.002) had decreased 6 months after the accident whereas the EQ-5D index had increased (p < 0.001). There were no statistically significant differences of the SOC or EQ-5D self-rated health scores over time. Conclusions In the care of patients suffering from a MVA with minor or no physical injuries, a caring touch intervention is associated with patients' report of decreased pain and improved wellbeing up to 6 months after the accident. Trial registration ClinicalTrials.gov Id:NCT02610205 . Date 25 November 2015.